Hardware-software complex for sports orientation, selection and stage control: potential for judo and sambo - Koryagina, Y.V.; Nopin, S.V.; Ter-Akopov, G.N.; Abutalimova, S.M. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop and implement an information system – hardware-software complex for sports orientation, selection and stage control in judo and sambo. Methods and structure of the study. The following methods were applied during the study: information technology based methods; spirometry; anthropometry, dynamometry, psychophysiological test methods; sports educational methods; non-parametric mathematical statistics methods. 240 children and junior athletes took part in testing the developed hardware-software complex. Results and conclusion. Using the data from the theoretical analysis and author’s research [3], an information testing system - hardware-software complex for sports orientation, selection and control in judo and sambo was developed. The hardware-software complex consists of the hardware facilities and software. The developed hardware-software complex includes four test blocks: morphological, functional, psychophysiological and physical fitness. The hardware-software complex for sports orientation includes four test blocks to determine the morphological, functional, psychophysiological, and physical fitness rates. The testing of thhardware-software complex for sports orientation, selection and stage control in judo and sambo showed its effectiveness in determining the psycho-functional readiness of children for judo and sports orientation, selection and control in judo and sambo.